Hypophosphatemic rickets: Revealing Novel Control Points for Phosphate Homeostasis - White, Kenneth E. (2014)
Rapid and somewhat surprising advances have recently been made towards understanding the molecular mechanisms causing heritable disorders of hypophosphatemia. The results of clinical, genetic, and translational studies have interwoven novel concepts underlying the endocrine control of phosphate metabolism, with far-reaching implications for treatment of both rare, Mendelian diseases as well as common disorders of blood phosphate excess such as chronic kidney disease (CKD). In particular, diseases caused by changes in the expression and proteolytic control of the phosphaturic hormone Fibroblast growth factor-23 (FGF23) have come to the forefront in terms of directing new models explaining mineral metabolism. These hypophosphatemic disorders, as well as others resulting from independent defects in phosphate transport or metabolism, will be reviewed herein, and implications for emerging therapeutic strategies based upon these new findings will be discussed.